Assessment of the tuned mass damper inerter for seismic response control of base‐isolated structures. Issue 2 (11th November 2020) - Masnata, Chiara; Di Matteo, Alberto; Adam, Christoph; Pirrotta, Antonina
Summary: In this paper, the hybrid control of structures subjected to seismic excitation by means of tuned mass damper inerter (TMDI) and base‐isolation subsystems is studied with the aim of improving the dynamic performance of base‐isolated structures by reducing the displacement demand of the isolation subsystem. The seismic performance of TMDI hybrid controlled structures is investigated in a comparative study, considering simple isolated systems and systems equipped with other absorber devices such as the tuned mass damper (TMD) and the tuned liquid column damper (TLCD). The TMDI has been optimized by performing a simplified approach based on minimizing the base‐isolation subsystem displacement variance, which provides simple analytical formulae for a quick definition of the TMDI parameters. The reliability of this approach is demonstrated by a comparison with a more accurate and computationally complex numerical optimization procedure. The control performance of three types of hybrid controlled structures exposed to a set of 44 recorded ground motions is investigated. Numerical results show that the TMDI can more efficiently control the structural response of low‐damped isolated structures, even compared to the TMD and the TLCD.